HDL DAN ATEROSKLEROSIS - Erizon Erizon; Yerizal Karani (Universitas Fort De Kock, 2020)
Atherosclerosis is a change that occurs in the arterial wall, which is characterized by the accumulation of extracellular lipids, recruitment and accumulation of leukocytes, foam cell formation, migration and proliferation of myocytes, extracellular matrix deposits (e.g. collagen, calcium), caused by a variety of pathogenesis that is chronic progressive, focal or diffuse and has acute or chronic manifestations that cause thickening and stiffness in arteries. Cardiovascular disease caused by atherosclerosis and thrombosis is a major cause of premature death and causes years of limitations in European countries and is also increasing in developing countries. Among many other independent risk factors for coronary heart disease (CHD) determined based on epidemiological studies, low HDL-C levels are one of the strongest. Based on the results obtained from the literature, HDL is an anti-atherogenic lipoprotein. HDL plays a role in preventing the process of atherosclerosis not only through the pathway of cholesterol transport but also through anti-inflammatory and antioxidant effects in the walls of blood vessels. This literature review focus on how is the role of HDL protection against atherosclerotic processes in the body